2020
DOI: 10.2503/hortj.utd-r006
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Nutrient Diagnosis of Fruit Trees Early in the Growing Season by Using Simultaneous Multi-element Analysis

Abstract: Fruit tree nutrition is one of the most important factors in terms of growth and productivity. Measurement of nutritional requirements is an important aspect of nutrient management because nutritional disorders reduce yield and fruit quality. This review explores how nutrient imbalances affect the yield and fruit quality of fruit trees, and presents methods for diagnosing fruit tree nutritional disorders in order to correct nutritional deficiencies. In orchards, differences between soil sampling sites and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…We successfully determined the optimal nutrient range in durian leaf cultivated on the VMD (Table 4). In this study, the proposed nutrients (g kg −1 ) that are optimal for leaf durian are 19.8-26.0 N, 2.11-2.90 P, 17.4-24.6 K, 20.8-32.6 Ca, 3.81-7.30 Mg, and 2.21-4.40 S. These optimum ranges for durian leaves at the stage 2 months before flowering agree with the results of Poovarodom et al [13], who reported the standard concentrations (g kg −1 ) of N (20-24), P (1.5-2.5), K (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), Ca (17)(18)(19)(20)(21)(22)(23)(24)(25), and Mg (2.5-5.0) in durian leaf cultivated in Thailand. Another study [46] in Thailand showed that the average nutrient concentrations (g kg −1 ) in durian leaf were 19-23, 1.7-2.6, 14-18, 20-35, 4.4-6.9, and 2.4-2.7 (N, P, K, Ca, Mg, and S, respectively).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We successfully determined the optimal nutrient range in durian leaf cultivated on the VMD (Table 4). In this study, the proposed nutrients (g kg −1 ) that are optimal for leaf durian are 19.8-26.0 N, 2.11-2.90 P, 17.4-24.6 K, 20.8-32.6 Ca, 3.81-7.30 Mg, and 2.21-4.40 S. These optimum ranges for durian leaves at the stage 2 months before flowering agree with the results of Poovarodom et al [13], who reported the standard concentrations (g kg −1 ) of N (20-24), P (1.5-2.5), K (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), Ca (17)(18)(19)(20)(21)(22)(23)(24)(25), and Mg (2.5-5.0) in durian leaf cultivated in Thailand. Another study [46] in Thailand showed that the average nutrient concentrations (g kg −1 ) in durian leaf were 19-23, 1.7-2.6, 14-18, 20-35, 4.4-6.9, and 2.4-2.7 (N, P, K, Ca, Mg, and S, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…In many countries, fertilizer recommendations and nutritional status diagnosis in fruit plants are determined based on leaf analysis [13][14][15] because foliar analysis reveals the actual uptake of the plant from fertilization and soil. This is considered a measurement method for the evaluation of the current nutritional status of crops, which might be replaced by soil analysis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Better understanding of nutrient interactions may be useful in understanding importance of balanced supply of nutrients and consequently improvement in plant growth or yields. The ionomes of nutrients in the root-zone soil solution were in uenced by soil type and fertilizer application management (Matsuoka et al 2020). A highly signi cant positive correlation was observed between soil-K and leaf-Mn (Nofal and Khalifa 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A highly signi cant positive correlation was observed between soil-K and leaf-Mn (Nofal and Khalifa 2002). Application of excessive amounts of N and P fertilizers especially in calcareous soil could alter the ionomic of nutrients and reduced the leaf K, Mn, Cu and Fe concentration in 'Jonathan' apple trees (Matsuoka et al, 2020). Also, increasing the rate of N fertilization when growth was constrained by K de ciency increased leaf N and decreased leaf B (Neilsen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation